Effects of Different Drying Methods on Physicochemical Properties and Microstructure of Penaeus vannamei - LIN Yawen, LIU Jiachen, LI Aiqing, GAO Yue, LI Jianrong, LI Xuepeng (Shipin Kexue, 2023)
In order to explore the effects of different drying methods on the physicochemical properties and microstructure of Penaeus vannamei, the drying characteristics, color, texture, water distribution, astaxanthin content, antioxidant capacity and microstructure of P. vannamei were analyzed after medium-short wave infrared drying (MSWID) or hot air drying (HAD). The results showed that with the increase in drying temperature, the moisture content of P. vannamei decreased gradually, and MSWID could reduce the drying time of P. vannamei by 16.67% and make its color brighter compared with HAD at 70 ℃. The hardness, gumminess and chewiness of P. vannamei were significantly increased with increasing drying temperature (P 0.05). According to magnetic resonance imaging (MRI) results, the rate of water migration during MSWID was faster than that during HAD. Besides, the results of microstructure observation indicated that the muscle fiber of P. vannamei became looser and more porous after MSWID compared with HAD. For both drying treatments, the α-helix relative content of shrimp proteins first increased and then decreased, and the β-fold relative content showed a contrary trend. The astaxanthin content of MSWID dried shrimp was lower than that of HAD dried shrimp, and so was the antioxidant capacity. The quality of MSWID dried P. vannamei was better than that of HAD dried P. vannamei, indicating MSWID to be a promising drying method for P. vannamei.